Efektivitas Artificial Intelligence (AI) Berbasis Project-Based Learning untuk Meningkatkan Keterampilan Mengembangkan Media Pembelajaran Berbasis Teknologi Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar - Rita Herlina Br PA; Hendrik Pantas; Nurabdullah Gimnastiar; Dina Gracela Surbakti; Andre Sitorus (Civiliza Publishing, Indonesia., 2026)
This study aimed to determine the effectiveness of Artificial Intelligence (AI)-based Project-Based Learning in improving the skills of developing technology-based learning media among students of the Primary School Teacher Education Study Program. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 60 undergraduate students, divided into an experimental class and a control class, with 30 students in each group. The experimental class was taught using AI-based Project-Based Learning, while the control class received conventional Project-Based Learning. Data were collected through pretests, posttests, product assessment rubrics, and observation sheets. The collected data were analyzed using descriptive statistics, normality and homogeneity tests, N-Gain analysis, and an Independent Samples t-test. The findings indicated that the experimental class achieved a higher mean posttest score (87.43) than the control class (78.27). The N-Gain score of the experimental class (0.66) was also higher than that of the control class (0.40). Furthermore, the Independent Samples t-test revealed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the two groups. The results demonstrate that integrating Artificial Intelligence into Project-Based Learning effectively enhances students' skills in developing technology-based learning media. This learning approach also promotes creativity, collaboration, digital literacy, and the production of more innovative instructional media, preparing prospective primary school teachers to meet the demands of technology-enhanced education.